Comprehensive Industrial Coaching for Msme Business Development in Pedagogical Perspective - Dangi Dangi; Ade Sobandi; Widhi Ariyo Bimo (Department of Tadris IPS FITK UIN Siber Syekh Nurjati Cirebon, 2024)
Comprehensive Industrial Coaching (CIC) is a collaborative model between entrepreneurial and pedagogic training. This study aims to analyse the role of CIC education and training for Micro Small and Medium Enterprises (MSME) business development. This quantitative research took a random sampling of 103 respondents from 110 MSME players who participated in CIC training. Data analysis was carried out using smart Partial Least Square Structure Equation Modelling (PLS SEM). The results showed that there is a positive influence relationship between the coaching model and MSME business development. The strongest relationship is shown by the relationship between the effect of increasing income on product diversification in the high category (2.015). While the lowest relationships shown by the relationship between training materials on the business mentoring model in the moderate category (0.070). The results of this study are expected to be a reference for the integration of modelling applied education and training innovations with pedagogical pillars for strengthening the competence of MSME actors.Keywords: CIC, pedagogic, MSME.